Etermination of Ca, Mg, Cu, Fe, Pb and Cd in fermented fish products by atomic absorption spectrometry / Muhamad Faiz Mohamed Iqbal - Mohamed Iqbal, Muhamad Faiz (2008)
Fermented fish products like budu and cincalok are produced from aquatic life. Budu is made from small fish while cincalok is made from shrimp. Although aquatic lives are good protein sources, but the excess intake of budu and cincalok may give negative health effect to consumers. It is because, there is probability for the sources of fish and shrimp exposed to water pollution besides undergo production process that use dangerous ingredients. Elements such as Mg, Ca, Cu, Fe, Pb and Cd may exist in these products. Research on concentration of these metals is done using Atomic Absorption Spectrometry. Before proceed to the metal analysis, budu and cincalok samples were digested by wet digestion process. Two types of samples were prepared for this process which was semi solid samples and freeze dried samples. The amount of Ca, Mg, Cu and Fe in freeze dried budu was 0.779, 2.945, 0.018 and 0.156 mg/g respectively while in semi solid budu was 0.186, 1.128, 0.008 and 0.027 mg/g respectively. The amount of Ca, Mg, Cu and Fe in freeze dried cincalok was 5.693, 5.636, 0.017 and 0.061 mg/g respectively while in semi solid cincalok was 1.782, 1.307, 0.005 and 0.019 mg/g respectively. Pb and Cd were not detected in all the samples prepared. The whole metals concentration detected is in range of allowable international standard. Concentration of element in all freeze dried samples show significant difference compared to the semi solid samples. Sample of budu and cincalok in freeze dried form showed higher concentration of metal detected. Freeze drying process give better result compared to the semi solid samples which was untreated. This result shows that budu and cincalok is safe to be eaten and become one of the good Mg and Ca contributors.